Study of 32 new phage tail-like bacteriocins (pyocins) from a clinical collection of Pseudomonas aeruginosa and of their potential use as typing markers and antimicrobial agents - Lucía Blasco; Manuel González de Aledo; Concha Ortiz-Cartagena; Inés Blériot; Olga Pacios; María López; Laura Fernández-García; Antonio Barrio-Pujante; Marta Hernández-Garcia; Rafael Cantón; María Tomás (Scientific Reports, 2023)
Abstract Phage tail-like bacteriocins (PTLBs) are large proteomic structures similar to the tail phages. These structures function in bacterial competition by making pores in the membrane of their competitors. The PTLBs identified in Pseudomonas aeruginosa are known as R-type and F-type pyocins, which have a narrow spectrum of action. Their specificity is determined by the tail fiber and is closely related to the lipopolysaccharide type of the target competitor strain. In this study, the genome sequences of 32 clinical of P. aeruginosa clinical isolates were analysed to investigate the presence of R-type and F-type pyocins, and one was detected in all strains tested. The pyocins were classified into 4 groups on the basis of the tail fiber and also the homology, phylogeny and structure of the cluster components. A relationship was established between these groups and the sequence type and serotype of the strain of origin and finally the killing spectrum of the representative pyocins was determined showing a variable range of activity between 0 and 37.5%. The findings showed that these pyocins could potentially be used for typing of P. aeruginosa clinical isolates, on the basis of their genomic sequence and cluster structure, and also as antimicrobial agents.